Aposentadoria especial após a EC 103/19 - Ladenthin, Adriane Bramante de Castro (2020)
Protecting oneself from the hardships of life has always been a constant concern of man who, after long years of studying mathematics and probability techniques, created private insurance, which initially aimed at securing work tools. Years later, using the same reasoning, they created social insurance (Social Security) in order to protect the individual risks that incapacitated the worker, caused by the ills of life: illness, disability, death, old age and unemployment. Gradually, it became clear that protection, intended only for workers, forsaken other sections of the population. In view of the diverse needs, the advance towards Social Security was a consequence of the evolution of human rights, which placed man as a true subject of law. In relation to workers exposed to the risks of harmful activity to health, several protection mechanisms were created, mainly after the industrial revolution, with several special retirement systems in the law. In national law, we have the benefits of an accident nature and special retirement as benefits intended for this protection. But even so, after many years, the work environment remains harmful, with significant numbers of accidents at work and unprotection. On the other hand, special retirement, created with marked and well-defined characteristics and whose risk is subjection to harmful physical, chemical, biological agents or associations of agents, harmful to health, has undergone several changes throughout history, since its emergence, that were making it difficult for workers to access it. The research developed here presents all these aspects mentioned above and studies the special retirement, its main requirements, specifically in the current reality of the worker who, after years of work exposed to agents harmful to health, upon reaching the exposure time that gives him the right to it, is now faced with this minimum age requirement, as required by Constitutional Amendment (EC) n. 103/19. The analysis developed in this research points to the need to apply EC 103/19 through interpretation by various methods, because in this setting of new rules promoted by it, with economic justification and without support in an actuarial study, this minimum age requirement was established the granting of special retirement and, as a result, changed its very nature, as it is now a benefit that now has a presumption of incapacity for work